2017
DOI: 10.1002/geot.201600019
|View full text |Cite
|
Sign up to set email alerts
|

Undrained behaviour of granular soils conditioned for EPB tunnelling – A new experimental procedure

Abstract: This paper presents a characterisation campaign carried out on granular soils conditioned for EPB tunnelling using a modified direct shear box. The main objective of soil conditioning is the reduction of its shear strength to control the counterpressure inside the bulk chamber. In order to preserve the pseudo-fluid characteristics of the conditioned soil mass, the main concerning parameters are their undrained properties. To characterise the undrained behaviour an adopted watertight direct shear apparatus was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…obtained results consistent with those of [34]. Recently, Carigi et al [35] studied the flow of a conditioned soil with cobbles using the test device of Figure 5 and developed assessment indexes.…”
Section: Tests On Claysupporting
confidence: 65%
See 2 more Smart Citations
“…obtained results consistent with those of [34]. Recently, Carigi et al [35] studied the flow of a conditioned soil with cobbles using the test device of Figure 5 and developed assessment indexes.…”
Section: Tests On Claysupporting
confidence: 65%
“…The shear and rheological behaviour of the conditioned soil influence the extraction process. To evaluate these parameters both vane test [29] [30] [31] [32] [33] and direct shear tests [9] [34] have been performed. Martinelli et al [34] used a modified undrained direct shear box and demonstrated that a good conditioning reduces the shear strength of the mix.…”
Section: Shear Rheometer and Flow Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compression testing and vane shear testing were combined to show the effect of the void ratio on the compressibility and shear strength of foam-conditioned soil. Martinelli et al [23] used a watertight direct shear apparatus to characterize undrained behavior in order to preserve the pseudofluid characteristics of the conditioned soil. Overall, the applicability of the vane shear test is valid.…”
Section: Introductionmentioning
confidence: 99%
“…For an optimal management and preliminary design of a tunnel it is necessary to have laboratory devices and procedures that can smoothly compare the positive effects on the soil conditioning on all these parameters. There is extensive research about the soil conditioning tests; the main informations can be found in Maidl (1995), Quebaud et al (1998), Jancsecz et al (1999), Milligan (2000), Psomas (2001), Bezuijen and Schaminée (2001), Peña (2003), Merritt and Mair (2008), Rivas et al (2009), Vinai et al (2008), Peila et al (2007Peila et al ( , 2009, Thewes and Budach (2010), Borio and Peila (2011), Thewes et al (2012), Hollmann and Thewes (2013), Todaro (2016), Peila (2014), Martinelli et al (2017).…”
Section: Introductionmentioning
confidence: 99%